1998
DOI: 10.1073/pnas.95.26.15502
|View full text |Cite
|
Sign up to set email alerts
|

RNA as a target of double-stranded RNA-mediated genetic interference in Caenorhabditis elegans

Abstract: Introduction of exogenous double-stranded RNA (dsRNA) into Caenorhabditis elegans has been shown to specifically and potently disrupt the activity of genes containing homologous sequences. In this study we present evidence that the primary interference effects of dsRNA are posttranscriptional. First, we examined the primary DNA sequence after dsRNA-mediated interference and found no evidence for alterations. Second, we found that dsRNAmediated interference with the upstream gene in a polar operon had no effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
248
2
9

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 513 publications
(262 citation statements)
references
References 34 publications
3
248
2
9
Order By: Relevance
“…[8][9][10][11][12][13][14][15][16] In addition to the use of antisense oligonucleotides and ribozymes, the application of small interfering RNA (siRNA) is an effective way to silence gene transcription. 17,18 Transcription silencing is thought to be a defense strategy that preserves genomes through evolution from attack by double-stranded RNA viruses and transposons. 19,20 Genetic and biochemical studies have confirmed that the mechanisms of gene silencing by siRNAs, cosuppression, and viruses share similarities.…”
mentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16] In addition to the use of antisense oligonucleotides and ribozymes, the application of small interfering RNA (siRNA) is an effective way to silence gene transcription. 17,18 Transcription silencing is thought to be a defense strategy that preserves genomes through evolution from attack by double-stranded RNA viruses and transposons. 19,20 Genetic and biochemical studies have confirmed that the mechanisms of gene silencing by siRNAs, cosuppression, and viruses share similarities.…”
mentioning
confidence: 99%
“…The binding of the siRNA triggers several steps for the digestion of mRNA and silences the expression of the target gene. 6,7 The siRNA in this process comes from a stem-loop RNA produced by a microRNA gene. Some of the microRNA genes are located in introns and are associated with their own promoters.…”
Section: Discussionmentioning
confidence: 99%
“…Processed by a dicer protein, the hairpin eventually becomes a small interfering RNA (siRNA) for RNA interference. 6,7 In other experiments, intronic IRs were shown to affect exon-intron splicing efficiency and determine alternative exon splicing. 8,9 More intriguingly, we found that some intronic LIRs are primate-specific, and probably critical in the evolution toward primates.…”
Section: Introductionmentioning
confidence: 96%
“…En 1998, Fire et al [14] ont montré qu'il est possible, chez C. elegans, d'inhiber post-transcriptionnellement l'expression d'un gène en injectant dans l'animal des molécules d'ARN double brin ayant une séquence commune avec le gène ciblé [15]. Cette inhibition est spéci-fique puisque seuls les gènes présentant de longues séquences communes avec l'ARN double brin sont éteints.…”
Section: L'interférence Par L'arnunclassified